Investigation on the Removal Performances of Heavy Metal Copper (II) Ions from Aqueous Solutions Using Hydrate-Based Method - Xiaobing Lan; Jun Chen; Yang Xie; Fenglong Hu; Changzhong Chen; Dongdong Li; Jianhong Jiang; Bin Deng (Molecules, 2023)
Since heavy metal ion-contaminated water pollutionis becoming a serious threat to human and aquatic lives, new methods for highly efficient removal of heavy metal ions from wastewater are important to tackle environmental problems and sustainable development. In this work, we investigate the removal performances of heavy metal copper (II) ions from aqueous solutions using a gas hydrate-based method. Efficient removal of heavy metal copper (II) ions from wastewater via a methane hydrate process was demonstrated. The influence of the temperature, hydration time, copper (II) ions concentration, and stirring rate on the removal of heavy metal copper (II) ions were evaluated. The results suggested that a maximum of 75.8% copper (II) ions were removed from aqueous solution and obtained melted water with 70.6% yield with a temperature of −2 °C, stirring speed 800 r/min, and hydration time of 4 h with aninitial copper concentration of 100 mg/L. The initial concentration of copper (II) ions in the aqueous solution could be increased to between 100 and 500 mg/L. Meanwhile, our study also indicated that 65.6% copper (II) ions were removed from aqueous solution and the yield of melted water with 56.7%, even with the initial copper concentration of 500 mg/L. This research work demonstrates great potential for general applicability to heavy metal ion-contaminated wastewater treatment and provides a reference for the application of the gas hydrate method in separation.